Perancangan Aplikasi Penjualan Online Berbasis Website: Bakso Mas Roy - Foris Juniawan Hulu; Fulgensius Oliver Dorman; Edwin Alexander (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research designs a website-based online sales application for Bakso Mas Roy. The goal is to expand market share, improve customer service, and operational efficiency. The methodology includes business needs analysis, interface design, system development, and testing. The results of the research are expected to help small and medium business owners utilize online sales to improve their business performance